2005
DOI: 10.1063/1.2035076
|View full text |Cite
|
Sign up to set email alerts
|

The elimination of a hydrogen atom in Na(H2O)n

Abstract: By a systematic examination on Na(H2O)n, with n = 4-7, 9, 10, and 15, we demonstrate that a hydrogen loss reaction can be initiated by a single sodium atom with water molecules. This reaction is similar to the well-known size-dependent intracluster hydrogen loss in Mg+(H2O)n, which is isoelectronic to Na(H2O)n. However, with one less charge on Na(H2O)n than that on Mg+(H2O)n, the hydrogen loss for Na(H2O)n is characterized by a higher barrier and a more flexible solvation shell around the metal ion, although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…Values of DE h (n), DE a (n) and DE r (n) (kcal/mol) are also given (see text at n = 8. Those numbers are high compared to the approximate barriers found in a previous study ($15(n = 6) and $8(n = 9) kcal/mol) [18]. The DE r (n) values also show a slow reduction with increasing n. The variations of DE a (n) and DE r (n) among the same sizes range over 4-6 and 3-7 kcal/mol, respectively, roughly speaking.…”
Section: Energeticssupporting
confidence: 52%
See 1 more Smart Citation
“…Values of DE h (n), DE a (n) and DE r (n) (kcal/mol) are also given (see text at n = 8. Those numbers are high compared to the approximate barriers found in a previous study ($15(n = 6) and $8(n = 9) kcal/mol) [18]. The DE r (n) values also show a slow reduction with increasing n. The variations of DE a (n) and DE r (n) among the same sizes range over 4-6 and 3-7 kcal/mol, respectively, roughly speaking.…”
Section: Energeticssupporting
confidence: 52%
“…The approximate activation energy was 11 kcal/mol. Liu's group extended their work to Na(H 2 O) n (n = 4-7, 9, 10 and 15), and found that the H-loss can be initiated by a single Na atom [18]. The barrier was reduced to $8 kcal/mol, since the hydrated electron moved to the outershell with increasing size.…”
Section: Introductionmentioning
confidence: 97%
“…30,31 The time scale of this process, which is characterized also by delocalization and redistribution of the excess electron density, is in a range of hundreds of femtoseconds. To this end, we monitored the positions of both oxygen and hydrogen atoms with respect to sodium along the trajectory.…”
Section: Dynamics Of Electron Delocalizationmentioning
confidence: 99%
“…24 Size selection was achieved by coupling the UV radiation of a dye laser below the threshold for ionization with the tunable IR radiation from an optical parametric oscillator. [26][27][28][29][30][31][32] The largest size treated was n = 8. 25 A number of theoretical studies addressed sodium-water clusters.…”
Section: Introductionmentioning
confidence: 99%
“…When Na and H 2 O meet, an Na/H 2 O interface forms between the different phases. SWR is composed of three steps: hydration, electron solvation, and OH bond breaking (Bewig et al, 1998;Bobbert and Schulz, 2001;Buck and Steinbach, 1998;Chan et al, 2005;Cwiklik et al, 2008a,b;Fukushima et al, 2012;Glendening and Feller, 1995;Hashimoto and Morokuma, 1994;Hashimoto et al, 2013;Kim et al, 2009;Maye and Mezei, 1996;Mundy et al, 2000;Rowley and Roux, 2012;Schulz et al, 2003;Siu and Liu, 2002;Vorontsov and Novakovskaya, 2009;Wheatley, 1996;White et al, 2000). First, water molecules surround the Na atom and solvate its valance electron.…”
Section: Effect On Swr Of Change In Physical Properties At the Liquidmentioning
confidence: 98%